Oral health status based on the Decayed, Missing and Filled Teeth (DMFT) Index and denture use in women of Shahedieh cohort study: a descriptive cross-sectional study in 2019 - Maryam Kazemipoor; Roghayeh Hakimian; Alireza Mirzaeeian; Fatemeh Owlia; Ali Dehghani; Masoud Mirzaei (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Oral health indicators such as DMFT and the use of denture have significant impact on the quality of individual and social life in women. This study was performed with aim to assess the prevalence of DMFT index and denture use according to fertility status in women of Shahedieh cohort study. Methods: This descriptive-cross sectional study was conducted in 2019 on the data from Shahedieh cohort study with the participation of 4935 women in the age range of 35 to 70 years. Variables related to fertility status such as: pregnancy, number of pregnancies, duration of breast feeding, and menopause were derived from Shahedieh questionnaire after permission. Prevalence of DMFT index and denture use was recorded in these participants. Data were analyzed using SPSS software (version 22) and statistical tests of Chi-square, T-test and ANOVA. P<0.05 was considered statistically significant. Results: The frequency of denture use was higher in non- pregnant women and women with the history of more than 4 pregnancies. Pregnant women had significantly lower DMFT than non-pregnant women (P= 0.051). With increasing the number of pregnancies and duration of breast feeding, DMFT index increased significantly (P-value =0.0001). Conclusion: Due to the very high average level of DMFT index and high prevalence of denture use in women of the present study, identification of risk factors related to oral health and adoption of preventive policies and interventions by health officials are crucial in the study area.